The benefits of thermal management to reduce friction losses in engines - Addison, James Edward (2015)
The research reported in the thesis addresses questions of how engine fuel consumption and carbon dioxide emissions are can be reduced through improvements in thermal management, lubricant design, and energy recovery. The investigations are based on simulation studies using computational models and sub-models developed or revised during the work, and results provided by complementary experimental studies carried out by collaborating investigators.